2017
DOI: 10.1016/j.semcdb.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of Sox transcription factors during the development of liver, bile duct, and pancreas

Abstract: The liver and pancreas are the prime digestive and metabolic organs in the body. After emerging from the neighboring domains of the foregut endoderm, they turn on distinct differentiation and morphogenesis programs that are regulated by hierarchies of transcription factors. Members of SOX family of transcription factors are expressed in the liver and pancreas throughout development and act upstream of other organ-specific transcription factors. They play key roles in maintaining stem cells and progenitors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 106 publications
2
20
0
1
Order By: Relevance
“…Moreover, the implanted human cells successfully recruited tunica external and media cells from the mouse body to form a mature vasculature structure, as evidenced by IF staining for human CD31 (endothelial layer, internal), anti‐mouse α‐SMA (smooth muscle cells, middle), and anti‐mouse vimentin (connective tissue, external; Figure h). Besides, the transcriptional levels of both Lgr5+/PRMT and Sox9/GATA4, which are important genes during intestinal and hepatic epithelium generation, were up‐regulated as Caco2 and Hep G2 grew. Similarly, early neurogenic markers, such as Fgf5 for primitive ectoderm and Sox1 for neuroectoderm, were expressed along the cultivation of SH‐SY5Y in THAG.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the implanted human cells successfully recruited tunica external and media cells from the mouse body to form a mature vasculature structure, as evidenced by IF staining for human CD31 (endothelial layer, internal), anti‐mouse α‐SMA (smooth muscle cells, middle), and anti‐mouse vimentin (connective tissue, external; Figure h). Besides, the transcriptional levels of both Lgr5+/PRMT and Sox9/GATA4, which are important genes during intestinal and hepatic epithelium generation, were up‐regulated as Caco2 and Hep G2 grew. Similarly, early neurogenic markers, such as Fgf5 for primitive ectoderm and Sox1 for neuroectoderm, were expressed along the cultivation of SH‐SY5Y in THAG.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, we observed PCB126-induced hypermethylation of sox9a and sox9b genes , which encode transcription factors critical for normal development. In mammals, SOX9 is responsible for maintaining homeostasis in the liver and the regenerative capacity is dependent on SOX9-positive hepatic progenitor cells [ 47 ]. Similarly, in the zebrafish regeneration model, ablation of hepatocytes causes transdifferentiation of biliary cells into hepatocytes and this process is blocked in sox9b mutants [ 48 ], suggesting an important role in liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…SOX9 has been implicated in control of liver progenitor cells and organ development [236]. A recent study reported that leptin stimulates SOX9 expression, and SOX9 suppresses PPARγ expression by binding to its promoter region to stimulate HSC activation [237].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%